Telomeres are shorter in Portuguese obese adults - Catarina Duarte; Maria Teresa Braz; Ana Marques-Ramos; José Silva-Nunes; Luisa Veiga; Miguel Brito (Journal of Mind and Medical Sciences)
Obesity is a clinical condition characterized by an abnormal accumulation of adipose tissue with an increased risk of developing illnesses such as type 2 diabetes, cardiovascular disease, and cancer. In obesity, the secretion of proinflammatory adipokines contributes to oxidative stress that can lead to a decline in the length of telomeres. Telomeres are structures of repetitive sequences delimiting the chromosomes, that plays a crucial role in maintaining their integrity and stability and, thus, its shortening is associated with cellular senescence and possible apoptosis. Although some studies indicate that obesity is associated with shorter telomeres, others contradict this data. Accordingly, the aim of our study was to determine whether obesity is associated with telomere shortening in Portuguese obese adults. For that, we collected buccal epithelial cells from 72 obese (Body Mass Index (BMI) greater than 30 kg / m2) and 74 norm weight individuals (BMI between 18.5 kg / m2 and 24.99 kg / m2) and determine telomere length through Real Time PCR. Results revealed that the relative telomere length of obese individuals is statistically significantly shorter than that of control non-obese group. By comparing obese subgroups, it was possible to observe that in the female subgroup the relative length of telomeres was shorter, in opposition to the male obese group, which indicates that the association between high BMI and shorter telomeres is genre-dependent. Furthermore, by studying the telomere length by age it was observed that there was no difference in the relative telomere length in obese under versus over 45 years old, demonstrating an age-independent association between obesity and telomere length. Accordingly, our results suggest that obesity is associated with telomeres shortening, and that this could be used as biomarker in obesity.